2015
DOI: 10.1155/2015/428106
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Protective Effect of Jiangya Tongluo Formula, through Regulation of Adrenomedullin and Angiotensin II, in Rats with Hypertensive Nephrosclerosis

Abstract: We investigated the effect of Jiangya Tongluo (JYTL) formula on renal function in rats with hypertensive nephrosclerosis. A total of 21 spontaneously hypertensive rats (SHRs) were randomized into 3 groups: valsartan (10 mg/kg/d valsartan), JYTL (14.2 g/kg/d JYTL), and a model group (5 mL/kg/d distilled water); Wistar Kyoto rats comprised the control group (n = 7, 5 mL/kg/d distilled water). Treatments were administered by gavage every day for 8 weeks. Blood pressure, 24-h urine protein, pathological changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was shown that YGY reduced excessive PSV in the interlobular arteries of rats with chronic renal failure, while increasing EDV through vasodilation and attenuating the effect of excessive ow resistance on the vascular endothelium. Notably, the PSV of EPO −/− mice was different from that of adenine-induced chronic renal failure rats, which may be due to a certain degree of hypertensive manifestation induced by adenine [45], but the blood pressure of adenine-induced chronic renal failure rats was not measured in this experiment, which is one of the shortcomings of this study.…”
Section: Ygy Improved Microcirculatory Disturbances In Adenine-induce...mentioning
confidence: 76%
“…It was shown that YGY reduced excessive PSV in the interlobular arteries of rats with chronic renal failure, while increasing EDV through vasodilation and attenuating the effect of excessive ow resistance on the vascular endothelium. Notably, the PSV of EPO −/− mice was different from that of adenine-induced chronic renal failure rats, which may be due to a certain degree of hypertensive manifestation induced by adenine [45], but the blood pressure of adenine-induced chronic renal failure rats was not measured in this experiment, which is one of the shortcomings of this study.…”
Section: Ygy Improved Microcirculatory Disturbances In Adenine-induce...mentioning
confidence: 76%
“…The mechanism includes alleviation of SHR and inhibition of 293T cells' effort induced by AngII through the epigenetic pathway associated with nicotinamide N-methyltransferase expression ( 47 ). The Jiangya Tongluo formula can regulate the protective effect of adrenomedullin and angiotensin in rats with hypertensive nephrosis ( 48 ). The heart-protecting musk pill can decrease the partial levels of AngII in SHR kidney, thus treating hypertensive nephropathy ( 49 ).…”
Section: Mechanism Of Herbal Medicine In the Treatment Of Hypertensivmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) and traditional herbs are beneficial for hypertensive renal damage in both symptoms and causes. TCM can lower the blood pressure and protect the kidney as an efficient and practical means of prevention [ 3 – 5 ]. The Yishen Pinggan Recipe (YPR) is a compound prepared from tradition Chinese herbs used for treating hypertension.…”
Section: Introductionmentioning
confidence: 99%